Analisis Perubahan Garis Pantai Pulau Enggano Bengkulu Utara Menggunakan Aplikasi Digital Shoreline Analysis System (DSAS) - Nur Aini Gunawan; Riska Ekawita; Supiyati Supiyati; Anjasman Anjasman (Universitas Andalas, 2024)
The coastline is the boundary between the land surface and the sea surface that can change every year. Enggano Island is one of the areas experiencing very rapid coastal changes. This research aims to identify changes in the coastline of Enggano Island over the past 5 years and determine the maximum and minimum changes in abrasion and accretion. The data processing results show that over the past 5 years, the coastline in three villages on Enggano Island has changed overall, with abrasion of 91.01 meters and accretion of 348.08 meters. Due to the wave height on Enggano Island, these three villages have experienced sedimentation (land addition) and changes in the coastline caused by accretion being greater than abrasion. For instance, in 2020-2021, the sea wave height peaked, causing abrasion. However, the wave height continued to decrease in the following years, causing land erosion each year. From the explanation above, it can be concluded that Enggano Island is experiencing changes in its coastline, which are predominantly caused by accretion events.